Physiotherapy Professionals: A Questionnaire for the Evaluation of Telerehabilitation Services in Egypt - Olfat Ibrahim Ali; Omnia Mustafa Salem; Salma Ashraf Abdelaziz Mohamed; Sabah Abdlnaser Hassan Ali; Eman Ahmed Embaby (International Journal of Telerehabilitation)
Purpose: This study aimed to evaluate the utilization of telerehabilitation services in Egypt and to investigate the concerns and barriers faced by Egyptian physiotherapists for implementation. Methods: This cross-sectional study recruited 306 Egyptian physiotherapists who were asked to complete an online survey including questions about the utilization of telerehabilitation services, awareness, perception, and attitude. Results: A total of 299 physiotherapists completed the online survey. Within the sample, 38.5% utilized telerehabilitation at work. Telerehabilitation was used frequently to deliver patient advice (17.6%), follow-up (16%), and exercise prescription (15.2%). Pain (16.2%) was the most common outcome assessed utilizing telerehabilitation. Additionally, 85.3% of physiotherapists agreed that the inclusion of telerehabilitation during the rehabilitation program is effective. The main barriers to implementing telerehabilitation in Egypt were lack of awareness (59.9%) and technical issues (58.2%). Conclusion: This study sheds light on the trends and challenges in utilizing telerehabilitation and may help in shaping the future of telerehabilitation in Egypt.